NMR studies of a timekeeping system - Vakonakis, I; LiWang, A (Springer-Verlag Berlin Heidelberg, 2009)
Cyanobacterial circadian clocks represent perhaps the best studied timekeeping system in terms of the molecular and mechanistic information available; structural biology has contributed significantly in both respects. We present here an overview of progress made using traditional high-resolution nuclear magnetic resonance (NMR) spectroscopy on the structures of these proteins in solution. Combining NMR and a dissection approach yielded high-resolution structures of many clock protein fragments, especially from KaiA, SasA and CikA, and the sole complex available thus far describing the interaction of KaiA with KaiC at high resolution. These structures allowed hypotheses on the mechanism and function of these proteins; we attempt to revisit these here. The development of NMR methodology has created new tools to access increasingly large and dynamic systems. We argue that these new approaches can be used in the study of circadian oscillators.